IMPLEMENTASI TEKNOLOGI WEB DALAM SISTEM TRANSAKSI BENGKEL SKALA MIKRO “BENGKEL MOTOR ANDI” - Novi Fitria Zulina Putri; Shofi Camila Laisya Amanda; Muchlis (Digital Business Insights Journal, 2026)
This article discusses the implementation of simple web technology for transaction data management in micro-scale motorcycle workshops. The case study was conducted at Andi's Motorcycle Workshop, which previously still used manual recording. The application is based on HTML, CSS, and JavaScript. The main features include simple login, service logging, search, local storage, export to Google Sheets, and PDF print. The development of this application is expected to improve the efficiency of data recording and management in small workshops that have not been reached by large-scale digital management systems.